Deoxy-sphingolipids, oxidative stress, and vitamin C correlate with qualitative and quantitative patterns of small fiber dysfunction and degeneration - Dohrn, Maike F.; Dumke, Christina; Hornemann, Thorsten; Nikolin, Stefan; Lampert, Angelika; Espenkott, Volker; Vollert, Jan; Ouwenbroek, Annabelle; Zanella, Martina; Schulz, Jörg B.; Gess, Burkhard; Rolke, Roman (Pain, 2022)
Defined by dysfunction or degeneration of Aδ and C fibers, small fiber neuropathies (SFNs) entail a relevant health burden. In 50% of cases, the underlying cause cannot be identified or treated. In 100 individuals (70% female individuals; mean age: 44.8 years) with an idiopathic, skin biopsy–confirmed SFN, we characterized the symptomatic spectrum and measured markers of oxidative stress (vitamin C, selenium, and glutathione) and inflammation (transforming growth factor beta, tumor necrosis factor alpha), as well as neurotoxic 1-deoxy-sphingolipids. Neuropathic pain was the most abundant symptom (95%) and cause of daily life impairment (72%). Despite the common use of pain killers (64%), the painDETECT questionnaire revealed scores above 13 points in 80% of patients. In the quantitative sensory testing (QST), a dysfunction of Aδ fibers was observed in 70% and of C fibers in 44%, affecting the face, hands, or feet. Despite normal nerve conduction studies, QST revealed Aβ fiber involvement in 46% of patients' test areas. Despite absence of diabetes mellitus or mutations in SPTLC1 or SPTLC2, plasma 1-deoxy-sphingolipids were significantly higher in the sensory loss patient cluster when compared with those in patients with thermal hyperalgesia (P < 0.01) or those in the healthy category (P < 0.1), correlating inversely with the intraepidermal nerve fiber density (1-deoxy-SA: P < 0.05, 1-deoxy-SO: P < 0.01). Patients with arterial hypertension, overweight (body mass index > 25 kg/m2), or hyperlipidemia showed significantly lower L-serine (arterial hypertension: P < 0.01) and higher 1-deoxy-sphingolipid levels (arterial hypertension: P < 0.001, overweight: P < 0.001, hyperlipidemia: P < 0.01). Lower vitamin C levels correlated with functional Aβ involvement (P < 0.05). Reduced glutathione was lower in patients with Aδ dysfunction (P < 0.05). Idiopathic SFNs are heterogeneous. As a new pathomechanism, plasma 1-deoxy-sphingolipids might link the metabolic syndrome with small fiber degeneration.